Pedagogical Activity as A Process of Constant Creativity - Azimbayeva Ranokhon Yuldashevna docent (Genius Journals, 2021)
The article considers pedagogical activity as a process of constant creativity. But unlike creativity in other areas (science, technology, art), the teacher's creativity does not have as its goal the creation of a socially valuable new, original, since its product is always the development of the personality. Of course, a creatively working teacher, and even more so an innovator, creates his own pedagogical system, but it is a means to obtain the best result in the given conditions
Keywords: Pedagogical activity; constant creativity; teacher's creativity; personality development